Systematic Review : Occupational Stress And Related Factors Among Hospital Nurses - Restila, Ridha (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2015)
Stress is one of the factors that affect the performance of nurses. According to Nursing Times 2014, more than 60% of nurses say they have experienced effects of work-related stress, such as physical or mental health problem.This systematic review research aimed at exploring factors related to occupational stress among hospital nurses involved 16 research. This research consist of 8 research from Indonesia in the year 2000-2013 and another 8 research obtained from international journals in the year 2010-2015.The entire research using cross sectional study design, sample size ranged from 24 - 2613. There are differences in the average number of research samples in the Indonesian research and international research (pvalue = 0,004). Total number of variables studied were 70 independent variables. The number of variables studied ranged from 4-25 per study. The most studied variables were marital status, salary, age, education, job demands, length of employment, shift work, promotion, and gender. From 9 variables most studied, promotion variable has a significant percentage of the highest p value, while the gender variable has no significant. Reference number used ranged from 7-59 references. No difference reference amount between Indonesian research and international research (p value = 0.806).